STRATEGY TO IMPROVE VOCABULARY MASTERY IN PRIMARY STUDENTS USING “DOMINO VOCABULARY CARD” - Julia Dwijayanti; Pravita Kanza; Moh Zainuddin; Julia Dwijayanti; Pravita Kanza; Moh Zainuddin (INTENS (International Journal of English Education and Linguistics), 2025)
Vocabulary is an important part of English but is often neglected in learning activities. Vocabulary mastery is very important to expedite English learning activities. In this article entitled "Strategy to Improve Vocabulary Mastery in Primary Students Using Domino Vocabulary Card," the reason for choosing this educational media in the form of pictorial word domino cards is because it is included in media that is creative, so the problem of the lack of mastery of English vocabulary owned by students and the lack of availability of learning media in the English learning process can be handled properly. With this media, it is hoped that it can help students become more enthusiastic about understanding English lessons and assist teachers in delivering material, thus expediting the course of teaching and learning activities.